Team Based Project dan Case Method Sebagai Strategi Pengembangan Keterampilan Mengembangkan Pembelajaran Mahasiswa - Cholifah Tur Rosidah; Pana Pramulia (Universitas Mathla'ul Anwar Banten, 2021)
The research is based on the importance of learning development skills that PGSD students must possess, while the phenomena found indicate that PGSD students are still less skilled in developing learning. Therefore, a learning strategy is needed that allows it to be effective in developing these skills. The study aims to analyze the implementation and effectiveness of the Team Based Project strategy and Case Method to develop the learning development skills of PGSD students. Quantitative research design in the form of Quasi Experimental Design. The research population is all PGSD students who take the Advanced Class Elementary School learning development course. Samples were obtained by cluster random sampling technique. Data collection techniques are carried out by means of documentation. The results of the effectiveness test based on the t-test showed that the skills of developing student learning who studied with the team based project strategy and case method had an average of 81.4. Higher than students who study with direct learning strategies with an average of 73.9.